A comparative study of managerial styles of insurance executives in Iloilo City masculine, feminine, androgynous - Bagaforo, Marie Cris; Colon, Mary Gem; Garmay, Rutchel; Manzo, Ma. Sheila; Tabinga, Agnes Melissa
One of the goals of a manager is to improve and maintain the growth of their company. This improvement involves changes in the structure of demand, productivity, and employee conditions. This study focuses on the managerial styles of the different insurance companies in Iloilo city. Through the questionnaires that were disseminated, we have found out the managerial styles used by different insurance managers in Iloilo City. The result was most male executives nowadays practice not only masculine managerial techniques but also managerial techniques commonly associated with women and vice-versa. Taken as a whole, the present study provides a comprehensive picture of the present scenario of every insurance company in Iloilo City which could become an essential element for further study.